Bullying and Health Related Quality of Life among Adolescents-A Systematic Review - Viney Prakash Dubey; Justina Kievišienė; Alona Rauckiene-Michealsson; Sigute Norkiene; Artūras Razbadauskas; Cesar Agostinis-Sobrinho (MDPI AG, 2022)
Health-related quality of life is among global health goals not only in adulthood but also in childhood and adolescence. Being a multi-component construct, health-related quality of life covers various domains, such as physical and psychological wellbeing and social and environmental areas. Bullying might significantly influence those domains especially in adolescence, a period of life when numerous personal and interpersonal transformations are experienced. Therefore, the aim of the current systematic review was to provide a comprehensive overview of the relationship of bullying with the health-related quality of adolescents' lives. An electronic literature search was performed using PubMed, Embase, and Cochrane Library, and 3621 full-text articles were identified. After a selection process, 12 studies covering diagnosis, prevention and treatment for each of the three sections "adolescents", "health related quality of life" and "bullying" were reviewed. An overall reduction in health-related quality of life in regard to bullying appeared from the studies analyzed, as well as a decline in adolescent mental health. Different bullying types were identified as causing harm to various adolescents' health-related quality of life domains. These findings may contribute to effective bullying management in schools and/or societal settings, and inform intervention strategies for maintaining the quality of life of adolescents being bullied.